Knowledge and attitudes of terminally ill patients and their family to palliative care and hospice services in Nigeria (2005)
Bacground: A palliative care and Hospice service is a neglected aspect of medical discipline especially in a developing country like Nigeria. With the global increase in incidence of cancer and HIV/A IDS and 70% of them presenting late, coupled with limited resources, for effective symptom control, palliative care therefore remains the only option left to improve the quality of life of the patients. Objective: To assess the, knowledge and attitudes of patients and their relations to palliative care and hospice services PC&H and to fashion out appropriate services for the patients. Materials and methods: A total of 130 participants were studied using a questionnaire which comprised of three parts: Socio-demographic variables. Information about Knowledge and Attitudes towards PC&H. Results: Sixty nine were patients while 61 were family members. Ninety four [72.3%] had no knowledge of PC&H regardless of level of education and social status. 109 (84%) agreed that symptoms of the terminally ill patients should be treated to improve their quality of life and 75%. of the participants agreed that this will be better done in a Hospice. 106 183% | participants desire to have hospice established in every community, this again was regardless of tribe Conclusion: There is a gross lack of knowledge about PC&H in our community as evidenced among, the participants studied. However, there is a positive attitude towards PC&H suggesting a general acceptance, since there is presently no well established Hospice, in Nigeria; we recommend that government and Non-governmental organizations should assist in this area. A hospital based Hospice might be a starting point